Music performance anxiety: development and validation of the Portuguese music performance anxiety scale - Barros, Samuel; França, Alex; Marinho, Helena; Pereira, Anabela (Frontiers in Psychology, 2024)
Several studies have developed and validated specific scales to understand, identify and confirm research hypotheses associated with music performance anxiety (MPA). These scales mostly assess behavioural, cognitive, and physiological factors. There is currently no original MPA assessment tool for higher music education in Continental Portuguese, which suggests a research gap. The aim of this study was to determine if the Portuguese Music Performance Anxiety Scale (PoMPAS), developed for this research, is a valid and reliable measure of MPA for the context of higher education in Portugal. The total sample was N=414 (166 male, 245 female, and three without gender identification). The development of this scale was based on a three-dimensional model (behavioural, cognitive, and physiological), following the theoretical models of Osborne and Kenny (2005) and Salmon (1990). Confirmatory factor analysis of the PoMPAS suggested a good fit in a three-dimensional model with 27 items. The internal consistency values proved appropriate, showing good Cronbach’s alphas (between α = .81 and α = .90). The McDonald’s Omega also demonstrated good consistency (between ω = .81 and ω = .90). The PoMPAS is a reliable tool to measure the impact of MPA, with good psychometric qualities, specifically for the Portuguese higher music education context.